Nanopore adaptive sequencing of gigabase length genomes for mixed samples, whole exome capture, and targeted panels - Payne, Stuart Alexander (2022)
Single molecule sequencing technologies, such as nanopore sequencing, provide new ways to investigate genomes and genetics. They permit the detailed analysis of stretches of DNA orders of magnitude larger than previously possible. Studying genomes at this detail allows for a better understanding of genome organisation and structural variants that are typically difficult to resolve using short read sequencing.